ANALISA TIPE FLUIDA MANIFESTASI PANASBUMI MENGGUNAKAN DIAGRAM TRILINIER CL-SO4-HCO3 DI DESA BAKAN KECAMATAN LOLAYAN KABUPATEN BOLAANG MONGONDOW - Aslam Rais; Heindrich Taunaumang; Jeferson Polii (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2021)
Indonesia is an area that could potentially be the source of the power of nature, including the source of power geothermal (geothermal). This is because Indonesia is a country located in the area of the world's ring of fire, where the tectonic plate stretches from the tip of the island of Sumatra, Java, to the Bandang Maluku area. Wrong one area in North Sulawesi, which has manifestations of geothermal, namely the village Bakan, the District Lolayan, District Bolaang Mongondow. In areas that are manifestations of geothermal eyes water hot. With the presence of one of the manifestations that the area that there is a potential for geothermal. Methods have used that method of geochemical and retrieval of data physical and samples of water hot in the field and then do the analysis laboratory on samples that. Based on the results of the research content of ions Cl, SO4 and HCO3 in a sample of water in the village Bakan which has been analyzed and the results of the calculation of the percentage of each ion that has been plotted into the diagram ternary showed that samples of water in the village Bakan is water sulfate (SO4), with the temperature manifestations 78 and the air temperature of 26 and pH showed value between 5 and 6 which means that the nature of the manifestations that are acidic due to having a pH less than 7.